Optimal taxation and debt with uninsurable risks to human capital accumulation - Piero Gottardi; Atsushi Kajii; Tomoyuki Nakajima (Federal Reserve Bank of Atlanta, 2014)
We consider an economy where individuals face uninsurable risks to their human capital accumulation and study the problem of determining the optimal level of linear taxes on capital and labor income together with the optimal path of the debt level. We show both analytically and numerically that in the presence of such risks it is beneficial to tax both labor and capital income and to have positive government debt.
Keywords: D52; D60; D90; E20; E62; H21; O40; 330; incomplete markets; Ramsey equilibrium; optimal taxation; optimal public debt